Extraction for the Evolution Features of Cavitation Cloud Induced by the Self-excited Oscillating Jet - Z. Hao; K. Li; R. Zhang; Y. Wang; G. Liu (Journal of Applied Fluid Mechanics)
The evolution process of the cavitation cloud in a fluidic oscillator is revealed via the high-speed photography experiment and the extraction of image gray value. The proper orthogonal decomposition (POD) method is employed to extract modal features and analyze the flow fields of a large amount of image data. The basic idea of the POD method is to transform the data into a set of orthogonal basis functions namely eigenmodes or principal components by performing a singular value decomposition of the data matrix. It is found that the first-order mode has a high contribution rate to the flow field, and its shape is nearly identical with the average gray level image of cavitation cloud. Therefore, the first-order mode represents the aggregate average of the gray level field of the cavitation cloud, which means that the large-scale lower order modal structure can reflect the overall stability characteristics of the cavitation cloud. However, the small-scale higher order modal structure reflects the dynamic characteristics such as the development and shedding of the cavitation cloud. With the increase of the inlet flow rate, the stability of the cavitation flow field decreases. By comparing the relationship between the mode coefficient and the average gray value, it is also discovered that the lower order mode coefficient can reflect the variations of cavitation intensity.